2006
DOI: 10.1029/2006gl027258
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability and trends in observed snow depth over North America

Abstract: This study uses a gridded dataset of daily U.S. and Canadian surface observations from 1960–2000 to study regional spatial and temporal variability and trends in snow depth across North America. Analysis shows minimal change in North American snow depth through January, with regions of decreasing snow depths beginning in late January. These regional decreases grow in intensity and extent through March and into April, implying an earlier onset of spring melt. The region showing the greatest decreases in snow de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 22 publications
10
149
0
1
Order By: Relevance
“…Our modeled decrease in the mean annual snow depth is consistent with climate model projections across the Northern Hemisphere (Arctic Climate Impact Assessment, 2004; Zhang et al, 2008b;Lawrence and Slater, 2010) and with observed trends from measurements conducted in the last decades (Dyer and Mote, 2006). A lengthening of the snow free period between 3.1 and 6.4 days for the last 30 years has been observed using satellite data for the period 1972-2000 in North America (Dye, 2002).…”
Section: Snowsupporting
confidence: 68%
“…Our modeled decrease in the mean annual snow depth is consistent with climate model projections across the Northern Hemisphere (Arctic Climate Impact Assessment, 2004; Zhang et al, 2008b;Lawrence and Slater, 2010) and with observed trends from measurements conducted in the last decades (Dyer and Mote, 2006). A lengthening of the snow free period between 3.1 and 6.4 days for the last 30 years has been observed using satellite data for the period 1972-2000 in North America (Dye, 2002).…”
Section: Snowsupporting
confidence: 68%
“…It has been documented that winter snow cover over North America is undergoing a change such that fall accumulation and spring ablation are occurring earlier Brown, 2000;Dyer and Mote, 2006). There are several possible reasons for the trend in snow cover over North America.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in snow depth over the same time period also exhibit decreasing trends, particularly throughout the central Canadian Prairies and Great Plains region of the United States (Dyer and Mote, 2006). Possible causes for the decrease in spring snow depth and snow extent in the latter part of the 20th Century include decreasing snowfall (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grundstein et al (2002) developed a research-oriented SWE climatology for the Great Plains of the United States by combining station observations with the 1-dimensional snow pack model SNTHERM (Jordan, 1991). A research-oriented product based on spatial interpolation of in situ depth measurements over North America (Dyer and Mote, 2006) has been used for process studies (Ge and Gong, 2008). The QuickSCAT active microwave scatterometer has been used to estimate the timing of snow melt across Greenland (Nghiem et al, 2001) and across Arctic lands .…”
Section: Other Combined Productsmentioning
confidence: 99%